The Rise of the Capital-State and Neo-Nationalism: A New Polanyian Moment - Svitych, Oleksandr (Brill, 2022)
Political Science
Keywords: critical social sciences; global studies; neo-nationalism; populism; social sciences; sociology & anthropology

Karl Polanyi and the Paradoxes of the Double Movement - Vail, John (Routledge, 2022)
This book offers a critical reconstruction of the double movement, the central thesis of Karl Polanyi’s The Great Transformation, one of the most influential books of the 20th century. The double movement is the establishment of a free market economy and the subsequent effort by society to ameliorate the destructive effects of the market. In Polanyi’s bold vision, the double movement constituted the hidden gear of social change and historical transformation within capitalism. The book is a forensic examination and critique of Polanyi’s argument. It develops an interpretive framework of the double movement as four interrelated social processes: the establishment of the self-regulating market, the rise of a market society that deepens and extends market imperatives, a social protection phase that constrains the market and safeguards society, and the contradictions and crises that result from this clash of social principles. The book will be an indispensable guide for students and scholars across the social sciences which illuminates the relevance of Polanyi’s insights to a critical understanding of the contemporary era –the scourge of insecurity and inequality, the multiple crises of neoliberalism, the rise of right wing populism- as well as those interested in egalitarian and emancipatory alternatives to capitalism.
Keywords: double movement; market society